Differential Effects of Methyl-4-Phenylpyridinium Ion, Rotenone, and Paraquat on Differentiated SH-SY5Y Cells - João Barbosa Martins; Maria de Lourdes Bastos; Félix Carvalho; João Paulo Capela (Journal of Toxicology)
Paraquat (PQ), a cationic nonselective bipyridyl herbicide, has been used as neurotoxicant to modulate Parkinson’s disease in laboratory settings. Other compounds like rotenone (ROT), a pesticide, and 1-methyl-4-phenylpyridinium ion (MPP+) have been widely used as neurotoxicants. We compared the toxicity of these three neurotoxicants using differentiated dopaminergic SH-SY5Y human cells, aiming to elucidate their differential effects. PQ-induced neurotoxicity was shown to be concentration and time dependent, being mitochondrial dysfunction followed by neuronal death. On the other hand, cells exposure to MPP+ induced mitochondrial dysfunction, but not cellular lyses. Meanwhile, ROT promoted both mitochondrial dysfunction and neuronal death, revealing a biphasic pattern. To further elucidate PQ neurotoxic mechanism, several protective agents were used. SH-SY5Y cells pretreatment with tiron (TIR) and 2-hydroxybenzoic acid sodium salt (NaSAL), both antioxidants, and Nω-nitro-L-arginine methyl ester hydrochloride (L-NAME), a nitric oxide synthase inhibitor, partially protected against PQ-induced cell injury. Additionally, 1-(2-[bis(4-fluorophenyl)methoxy]ethyl)-4-(3-phenyl-propyl)piperazine (GBR 12909), a dopamine transporter inhibitor, and cycloheximide (CHX), a protein synthesis inhibitor, also partially protected against PQ-induced cell injury. In conclusion, we demonstrated that PQ, MPP+, and ROT exerted differential toxic effects on dopaminergic cells. PQ neurotoxicity occurred through exacerbated oxidative stress, with involvement of uptake through the dopamine transporter and protein synthesis.